50 Predicting psychiatric and cognitive outcomes after surgery for frontal lobe epilepsy. (28th May 2019) - Bindman, D; Foong, J; Thompson, P
Abstract : Aims: Previous research suggests that the side and site of epilepsy surgery may have important implications for post-surgical psychiatric and behavioural outcomes. Most of the published studies are in temporal lobe epilepsy surgery providing some evidence of frontal lobe dysfunction associated with postoperative mood disorder. Our study aims to identify potential clinical and cognitive predictors of postoperative psychiatric outcome following frontal lobe epilepsy surgery. Methods: A retrospective review of 78 consecutive patients who had undergone frontal lobe epilepsy (FLE) surgery at the National Hospital for Neurology and Neurosurgery between 1997 and 2016. Notes were scrutinised for pre- and postoperative psychiatric diagnoses, neuropsychological test findings, seizure data, histopathological data, and MRI and video-EEG data. Chi-square analysis and paired-sample t- tests will be used to examine the relationship between variables and to investigate differences between pre- and postoperative cognitive test scores. Results: Data analysis is in progress and final results will be presented in the conference poster. Preliminary data shows an incidence of post-operative psychopathology in the region of 29% with 14% of patients developing a de novo psychiatric condition within 48 months follow up. Preoperative non-executive function deficits were significantly associated with de novo psychopathology in our initial analysis (χ2 (1)=4.99, p=0.03). Conclusions: Initial analysis has identified aspects of pre-operative cognitive function that could act as predictors of post-operative psychiatric comorbidity. The results of the completed data analysis will be presented including data on the site of surgery and its relationship to post-operative psychopathology. Identification of patients at high risk of poor outcome will allow greater precision in patient selection and more pro-active treatment approaches in the post-operative period.